2016
DOI: 10.1523/jneurosci.2025-16.2016
|View full text |Cite
|
Sign up to set email alerts
|

Granular Layer Neurons Control Cerebellar Neurovascular Coupling Through an NMDA Receptor/NO-Dependent System

Abstract: Neurovascular coupling (NVC) is the process whereby neuronal activity controls blood vessel diameter. In the cerebellum, the molecular layer is regarded as the main NVC determinant. However, the granular layer is a region with variable metabolic demand caused by large activity fluctuations that shows a prominent expression of NMDA receptors (NMDARs) and nitric oxide synthase (NOS) and is therefore much more suitable for effective NVC. Here, we show, in the granular layer of acute rat cerebellar slices, that ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
80
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2
1

Relationship

4
5

Authors

Journals

citations
Cited by 71 publications
(84 citation statements)
references
References 80 publications
4
80
0
Order By: Relevance
“…To validate this preliminary information at protein level, we carried out immunohistochemistry on the rat cerebellar granular layer by using a rabbit polyclonal antibody raised against the N-terminal domain of human TRPM4 (Kim et al, 2013). GrCs were identified by co-staining the slices with DAPI, as recently described in (Mapelli et al, 2017). Confocal microscopy revealed that TRPM4 protein was expressed in GrCs both on the plasma membrane and within the cytosol (Fig.…”
Section: Trp Current Expression In Accelerating Grcsmentioning
confidence: 88%
“…To validate this preliminary information at protein level, we carried out immunohistochemistry on the rat cerebellar granular layer by using a rabbit polyclonal antibody raised against the N-terminal domain of human TRPM4 (Kim et al, 2013). GrCs were identified by co-staining the slices with DAPI, as recently described in (Mapelli et al, 2017). Confocal microscopy revealed that TRPM4 protein was expressed in GrCs both on the plasma membrane and within the cytosol (Fig.…”
Section: Trp Current Expression In Accelerating Grcsmentioning
confidence: 88%
“…Some researchers even argue that capillary flow is regulated by contractile pericytes on first and second order capillaries (Peppiatt et al, 2006;Hall et al, 2014;Mishra et al, 2016;Khennouf et al, 2018). Mechanisms involved in neurovascular coupling tend to vary by the signaling cell type and location within the brain (Devonshire et al, 2012;Uhlirova et al, 2016;Mapelli et al, 2017). Furthermore, the relative importance of each pathway in producing functional hyperemia is still in question (Attwell et al, 2010;Iadecola, 2017;Longden et al, 2017;Mapelli et al, 2017;Hogan-Cann et al, 2019).…”
Section: Regulation Of Cerebral Blood Flow and Neurovascular Couplingmentioning
confidence: 99%
“…It has been found that capillary dilation occurs following the effect on pericytes of E2 prostaglandins, released by astrocytes, whereas arteriolar dilation occurs following the effect of nitric oxide (NO) released by inter-neurons. Furthermore, the dilation of capillaries by pericytes occurs faster than that of arterioles and offers a greater increase in blood flow [37]. Moreover, the effect of NO, released by the neurons of the granular layer, is two-fold, in that, in addition to causing vasodilation, it inhibits the synthesis of the powerful vasoconstrictor 20-Hydroxyeicosatetraenoic acid (20-HETE), which is produced in pericytes by the metabolism of arachidonic acid [38].…”
Section: Blood Flow Regulationmentioning
confidence: 99%